Endothelial SHANK3 regulates tight junctions in the neonatal mouse blood-brain barrier through β-Catenin signaling - Yong-Eun Kim; Minseong Kim; Sunwhi Kim; Raham Lee; Yusuke Ujihara; Esther Magdalena Marquez-Wilkins; Yong-Hui Jiang; Esther Yang; Hyun Kim; Changhoon Lee; Changwon Park; Il Hwan Kim (Nature Communications)
Abstract Autism spectrum disorder (ASD) is a neurodevelopmental disability condition arising from a combination of genetic and environmental factors. Despite the blood-brain barrier (BBB) serving as a crucial gatekeeper, conveying environmental influences into the brain parenchyma, the contributions of BBB in ASD pathogenesis remain largely uncharted. Here we report that SHANK3, an ASD-risk gene, expresses in the BBB-forming brain endothelial cells (BECs) and regulates tight junctional (TJ) integrity essential for BBB’s barrier function. Endothelium-specific Shank3 (eShank3) knockout (KO) neonatal mice exhibit male-specific BBB-hyperpermeability, reduced neuronal excitability, and impaired ultra-sonic communications. Although BBB permeability is restored during adult age, the male mutant mice display reduced neuronal excitability and impaired sociability. Further analysis reveals that the BBB-hyperpermeability is attributed to the β-Catenin imbalance triggered by eShank3-KO. These findings highlight a pathogenic mechanism stemming from the ASD-risk Shank3, emphasizing the significance of neonatal BECs in the BBB as a potential therapeutic target for ASD.